Antibacterial non-woven nanofibers of curcumin acrylate oligomers1. (2nd June 2015) - Killi, Naresh; Paul, Vejendla Luke; Gundloori, Rathna Venkata Naga
<x xml:space="preserve">Abstract</x> Oligomers of curcumin acrylates were blended with polylactide and electrospun to nanofiber mats, which were antibacterial and highly porous.